Attenuating PI3K/Akt- mTOR pathway reduces dihydrosphingosine 1 phosphate mediated collagen synthesis and hypertrophy in primary cardiac cells. (May 2021) - Magaye, Ruth R.; Savira, Feby; Hua, Yue; Xiong, Xin; Huang, Li; Reid, Christopher; Flynn, Bernard L.; Kaye, David; Liew, Danny; Wang, Bing H.
Abstract: Cardiac fibrosis and myocyte hypertrophy play contributory roles in the progression of diseases such as heart Failure (HF) through what is collectively termed cardiac remodelling. The phosphoinositide 3- kinase (PI3K), protein kinase B (Akt) and mammalian target for rapamycin (mTOR) signalling pathway (PI3K/Akt- mTOR) is an important pathway in protein synthesis, cell growth, cell proliferation, and lipid metabolism. The sphingolipid, dihydrosphingosine 1 phosphate (dhS1P) has been shown to bind to high density lipids in plasma. Unlike its analog, spingosine 1 phosphate (S1P), the role of dhS1P in cardiac fibrosis is still being deciphered. This study was conducted to investigate the effect of dhS1P on PI3K/Akt signalling in primary cardiac fibroblasts and myocytes. Our findings demonstrate that inhibiting PI3K reduced collagen synthesis in neonatal cardiac fibroblasts (NCFs), and hypertrophy in neonatal cardiac myocytes (NCMs) induced by dhS1P, in vitro . Reduced activation of the PI3K/Akt- mTOR signalling pathway led to impaired translation of fibrotic proteins such as collagen 1 (Coll1) and transforming growth factor β (TGFβ) and inhibited the transcription and translation of tissue inhibitor of matrix metalloproteinase 1 (TIMP1). PI3K inhibition also affected the gene expression of S1P receptors and enzymes such as the dihydroceramide delta 4 desaturase (DEGS1) and sphingosine kinase 1 (SK1) in the de novo sphingolipid pathway. While in myocytes, PI3K inhibition reduced myocyte hypertrophy induced by dhS1P by reducing skeletal muscle α- actin (αSKA) mRNA expression, and protein translation due to increased glycogen synthase kinase 3β (GSK3β) mRNA expression. Our findings show a relationship between the PI3K/Akt- mTOR signalling cascade and exogenous dhS1P induced collagen synthesis and myocyte hypertrophy in primary neonatal cardiac cells.